Mechanism of skeletal muscle atrophy after spinal cord injury: A narrative review - Xu, Xin; Talifu, Zuliyaer; Zhang, Chun-Jia; Gao, Feng; Ke, Han; Pan, Yun-Zhu; Gong, Han; Du, Hua-Yong; Yu, Yan; Jing, Ying-Li; Du, Liang-Jie; Li, Jian-Jun; et al. (Frontiers in Nutrition, 2023)
Spinal cord injury leads to loss of innervation of skeletal muscle, decreased motor function, and significantly reduced load on skeletal muscle, resulting in atrophy. Factors such as braking, hormone level fluctuation, inflammation, and oxidative stress damage accelerate skeletal muscle atrophy. The atrophy process can result in skeletal muscle cell apoptosis, protein degradation, fat deposition, and other pathophysiological changes. Skeletal muscle atrophy not only hinders the recovery of motor function but is also closely related to many systemic dysfunctions, affecting the prognosis of patients with spinal cord injury. Extensive research on the mechanism of skeletal muscle atrophy and intervention at the molecular level has shown that inflammation and oxidative stress injury are the main mechanisms of skeletal muscle atrophy after spinal cord injury and that multiple pathways are involved. These may become targets of future clinical intervention. However, most of the experimental studies are still at the basic research stage and still have some limitations in clinical application, and most of the clinical treatments are focused on rehabilitation training, so how to develop more efficient interventions in clinical treatment still needs to be further explored. Therefore, this review focuses mainly on the mechanisms of skeletal muscle atrophy after spinal cord injury and summarizes the cytokines and signaling pathways associated with skeletal muscle atrophy in recent studies, hoping to provide new therapeutic ideas for future clinical work.